(untitled) (Medical science of Uzbekistan, 2024)
Atopic dermatitis (AD) is the most common skin disease in childhood and requires family support to manage it. This disease significantly affects the quality of life (QOL) of children and families, but there is a lack of literature on the social and emotional impact of the disease on family members and caregivers. Objective: To assess the emotional and social impact of AD on mothers of children with this disease. Method: This is a qualitative study of semi-structured interviews with mothers of children diagnosed with AD. The following variables were assessed: diagnosis and initiation of treatment, knowledge about the disease and impact on the lives of mothers. The materials were analyzed using the Lawrence Bardeen content analysis method. Disease severity was assessed using the SCORAD scale. Results: 23 interviews were conducted with mothers of children diagnosed with AD. In 82.6% of cases, conflicts arose when the mothers first came into contact with the disease. In 43.5% of cases, mothers were responsible for the treatment of their children. About 56.6% perceived AD as a cause of suffering and difficulties, and 21.7% perceived AD as a learning experience. Conclusion: AD is a chronic disease that affects the psychological and social life of mothers. In the treatment of AD, mothers should be assessed and provided with psychological support to improve long-term adherence to treatment.